Exploring Students’ Perception on Online EFL Learning through WhatsApp Application - Linda Meylinda (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2023)
The present study attempted to find out students’ perception in their learning English process through WhatsApp application. The study was conducted based on some facts that there are recently learning delivered by some teaching techniques because of Covid 19 pandemic. Due to the pandemic of Covid 19 has changed the system of education in the world, Indonesia is one of the countries that was influenced and applied distance learning system. The study was conducted in one of the private universities in Tangerang Selatan. There were 20 participants involving in this study who came from the second semester of academic year 2021-2022. To find some accurate data, the researchers collected a data through semi-structure interviews via Google Meet. The students were asked to join some learning activity such as speaking, writing, listening and reading. Then, they were interviewed about what they feel and their experiences during online learning. A qualitative study which focuses on a design narrative was used to get students’ point of view regarding learning English through WhatsApp application. The result showed that the students have a good perception of learning English using WhatsApp. The use of WhatsApp in learning English is very influential on students.